1990
DOI: 10.1080/00223891.1990.9674106
|View full text |Cite
|
Sign up to set email alerts
|

MacAndrew Versus MacAndrew: The Relative Efficacy of the MAC and the SAP Scales for the MMPI in Screening Male Adolescents for Substance Misuse

Abstract: MacAndrew (1965) constructed the MacAndrew Alcoholism Scale (MAC) using adult male alcoholic outpatients and male psychiatric outpatients. Later, he developed the Substance Abuse Proclivity Scale (SAP; MacAndrew, 1986), specifically for screening younger males, using adolescent and young adult substance misusing and nonmisusing males 16 to 22 years of age. Because clinicians frequently apply the MAC to adolescents, we compared the efficacy of the MAC and the SAP scales using a sample of 436 young males between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The validity and use of scores from the MAC/MAC-R has been called into question by others (Schwartz & Graham, 1979), a conclusion supported by a variety of studies (Colligan & Offord, 1990;Svanum & Ehrmann, 1993). Gottesman and Prescott (1989) stated that abuses of the MAC/MAC-R in both research and applied settings exist due to the false assumption that the measure's scores contain sufficient construct and predictive validities despite the existence of contrary meta-analytic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The validity and use of scores from the MAC/MAC-R has been called into question by others (Schwartz & Graham, 1979), a conclusion supported by a variety of studies (Colligan & Offord, 1990;Svanum & Ehrmann, 1993). Gottesman and Prescott (1989) stated that abuses of the MAC/MAC-R in both research and applied settings exist due to the false assumption that the measure's scores contain sufficient construct and predictive validities despite the existence of contrary meta-analytic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the accuracy and usefulness of the MAC. Some reported positive findings (Rosenberg, 1972;Schwartz & Graham, 1979), whereas others have reported negative findings (e.g., Colligan & Offord, 1990). After reviewing 74 studies published between 1976 and 1987, Gottesman and Prescott (1989) concluded that scores on the MAC have dubious validity.…”
mentioning
confidence: 99%